Epitaxial growth of aligned GaN nanowires and nanobridges - Kim, Kyungkon; Henry, Tania; Cui, George; Han, Jung; Song, Yoon-Kyu; Nurmikko, Arto V.; Tang, Hong (WILEY-V C H VERLAG GMBH, 2007)
Homo-epitaxialy grown aligned GaN nanowires were prepared on crystalline GaN mesas. The GaN nanowires showed preferential growth along the (10 (1) over bar0) direction (m-axis direction). By using selectively positioned and crystallographically well defined GaN epitaxial lateral overgrowth (ELO) mesas as substrate, we obtained horizontally aligned GaN nanowires, in comb-like arrays and hexagonal network interconnecting the ELO mesas. Preliminary testing of the nanomechanical behavior of horizontal nanowires is reported. Combination of ELO with nanowire synthesis is expected to provide a new paradigm for nanoelectronic and electromechanical devices. (c) 2007 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: GALLIUM NITRIDE NANOWIRES; CHEMICAL-VAPOR-DEPOSITION; CATALYTIC SYNTHESIS; MOVPE